Understanding the Conflict in Aceh through Primordialism, Ethno-symbolism, and Constructionism - Yenni Rosana (Utan Kayu Publishing, 2025)
This study examines the conflict between Aceh and Indonesia through the lens of three theoretical perspectives: primordialism, ethno-nationalism, and constructionism. Using video collections from the Journeyman Pictures YouTube channel, the research analyzes visual narratives of the conflict, including human rights abuses, natural resource exploitation, and political struggles. While it was initially expected that one theory would be more dominant, the findings reveal an interconnection between these perspectives. Primordialism is the most evident in the videos, as Acehnese identity is portrayed as distinct from the rest of Indonesia, reinforced by grievances over economic injustice and military oppression. Ethno-nationalist and constructionist elements are also present, particularly in framing Aceh’s resistance as a response to territorial nationalism. The study highlights the role of elite persuasion in Aceh’s integration into Indonesia, reinforcing constructionist arguments that nationalism is socially constructed. Additionally, the research underscores the significant impact of human rights abuses on prolonging the conflict. By integrating multiple theoretical perspectives, this research contributes to a deeper understanding of Aceh’s struggle and broader discussions on nationalism, conflict, and reconciliation